Diffusion of 63Ni in severely deformed ultrafine grained Cu-based alloys. (15th January 2017) - Straumal, P.B.; Wegner, M.; Shangina, D.V.; Kogtenkova, O.A.; Kilmametov, A.; Divinski, S.V.; Dobatkin, S.V.; Wilde, G.
Abstract: Cu-Hf and Cu-Cr-Hf alloys have been subjected to severe plastic deformation applying equal channel angular pressing and high pressure torsion. Grain boundary diffusion was measured in a temperature interval between 423 K and 570 K using the radiotracer technique with the 63 Ni isotope as tracer. The microstructure evolution examination using scanning electron microscopy showed no structural changes during diffusion annealing. Diffusion profiles in pressed samples reveal the occurrence of a percolating porosity, whereas no such porosity could be detected in the twisted samples. The determined diffusion coefficients correspond to those in severely plastically deformed Cu alloyed with Pb or Zr. Graphical abstract: